A Retroperitoneal Isolated Enteric Duplication Cyst Mimicking a Teratoma: A Case Report and Literature Review - Daichi Momosaka; Yasuhiro Ushijima; Akihiro Nishie; Yoshiki Asayama; Kousei Ishigami; Yukihisa Takayama; Daisuke Okamoto; Nobuhiro Fujita; Tetsuo Ikeda; Keiichiro Uchida; Masaaki Sugimoto; Kenichi Kohashi; et al. (Case Reports in Radiology)
Enteric duplication cysts lacking anatomic association with the gastrointestinal tract are called isolated enteric duplication cysts (IEDCs). We present an atypical case of a retroperitoneal IEDC with a tortuous tubular complex shape that enfolded the surrounding retroperitoneal fat and mimicked a retroperitoneal teratoma. Multiplanar reconstruction images should be used to evaluate such a lesion correctly. A tortuous tubular complex shape could be a key finding to differentiate from other retroperitoneal cysts.